The Culture Of Frugality In The Consumption Patterns Of The "Murah - Murah" Online Community: A Netnographic Study On Social Media X - Shafinaz Nafizhah Hardianti; Augustin Mustika Chairil; Adhara Suwanta (International Journal of Social, Economic, and Business, 2026)
This study aims to understand how the culture of frugality is formed, particularly in the consumption patterns of members of the online community “Murah-Murah.” This research uses a descriptive qualitative method with a netnography approach to explore more deeply the practices, interactions, and values that shape the culture of frugality within the community. The data were obtained through observations of posts and interactions among community members related to buying and selling activities. The findings show that the practice of frugality is reflected in various forms of digital interaction, such as the tawarin phenomenon, want to buy (WTB) posts, and want to sell (WTS) posts from the sellers’ point of view. These phenomena show that community members actively participate in negotiation processes, searching for goods at more affordable prices, and offering items at prices considered inexpensive. This process occurs through posts made by members and responses from othermembers in the community. These interactions reflect values of saving, efficiency, and efforts to maximize the value of each transaction. Therefore, the “Murah-Murah” community can be understood as a virtual space thatfacilitates the formation of a frugality culture through digital consumption practices and social interactions among its members.